Crisis del órgano de apelación de la OMC: Reforma del ESD (Forseti. Law Review, 2026)
This paper examines the ongoing crisis of the Appellate Body of the World Trade Organization and its impact on the dispute settlement system. It analyzes how the paralysis of the Appellate Body has undermined the effectiveness of the procedure established under the Dispute Settlement Understanding, which includes consultations and panel proceedings. It also assesses the ongoing negotiations aimed at reforming this mechanism.
Keywords: World Trade Organization; Appellate Body; Trade disputes; Trump; USA